2017
DOI: 10.1111/hir.12177
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the ‘grey literature’ of poster presentations: a mapping review

Abstract: If the aim of poster presentation is to share and discuss information with others, then the limitations of poster abstracts and questions raised in the retrieved literature suggest that further efforts are required to make this more effective. Library and information specialists of all disciplines are likely to play a key role in such developments, and especially those from the medicine and health care disciplines which feature so prominently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…While conference proceedings did not play a prevalent role in our study, there is evidence that this venue has the potential to be a vital component of scholarly communication [18], with Ania proposing that "proceedings…provide the medium for reporting [grey literature]" [19]. Pelzer and Wiese's bibliometric study of veterinary literature reported that 50.1% of grey literature citations fell in the conference category [15], which was much higher than the frequency of conference proceedings citations in peer-reviewed nursing journals that was found in our study.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…While conference proceedings did not play a prevalent role in our study, there is evidence that this venue has the potential to be a vital component of scholarly communication [18], with Ania proposing that "proceedings…provide the medium for reporting [grey literature]" [19]. Pelzer and Wiese's bibliometric study of veterinary literature reported that 50.1% of grey literature citations fell in the conference category [15], which was much higher than the frequency of conference proceedings citations in peer-reviewed nursing journals that was found in our study.…”
Section: Discussionmentioning
confidence: 66%
“…Pelzer and Wiese's bibliometric study of veterinary literature reported that 50.1% of grey literature citations fell in the conference category [15], which was much higher than the frequency of conference proceedings citations in peer-reviewed nursing journals that was found in our study. Based on the results of Rowe's recent mapping study of poster presentation citations [18], however, the frequency with which conference proceedings are cited in nursing journals may grow over time.…”
Section: Discussionmentioning
confidence: 99%
“…Academic posters are a popular way to present research findings in a quick and brief form. With an estimated 1.1 million poster presentations at conferences each year, they are second only to journal articles as a chosen form of research communication [16]. However, the information they convey is limited by the constraints of the medium, which cannot accommodate the amount of information contained in a journal article [17].…”
Section: The Interactive Poster Formatmentioning
confidence: 99%
“…Dissemination of evidence, means of access and the effectiveness of that access are all explored in this quarter's issue of the Health Information and Libraries Journal.…”
Section: In This Issue…mentioning
confidence: 99%
“…Rowe undertook a mapping review to examine the patterns and extent that posters are used to present information . Results were categorised by discipline, year of publication and the nature of the return.…”
Section: In This Issue…mentioning
confidence: 99%